Materials science and technology :a comprehensive treatment /. Vollume 2A., Characterization of meterials part I / edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol. editor : Eric Lifshin - Lifshin, Eric
Vol. 2A Characterization of meterials part I in 1992